Dyspepsia: terminology, causes and risk factors, patient management - L. A. Syunyaeva; N. V. Shulpekova; T. L. Lapina (Медицинский совет, 2022)
Clarification of the term dyspepsia is associated with the development of ideas about functional diseases of the gastrointestinal tract (GIT) and the development and implementation of the Rome criteria for these diseases. Dyspepsia is a complex of symptoms related to the gastroduodenal region and includes epigastric pain and burning sensation, epigastric fullness after eating, and early satiety. Dyspepsia is widespread, with about 20% of the adult population having these symptoms. It is important to note that in the majority of individuals with dyspepsia (up to 80%), the organic, systemic or metabolic cause of symptoms cannot be identified using traditional diagnostic methods, indicating its functional nature. In H. pylori-infected patients with dyspepsia, symptoms may be associated with gastritis if successful eradication is followed by sustained remission (H. pylori-associated dyspepsia). If dyspepsia persists after etiological treatment of bacterial gastritis, a diagnosis of functional dyspepsia should be established. A feature of functional dyspepsia is the frequent overlap of its clinical variants (postprandial distress syndrome (PPDS) and epigastric pain syndrome SBE) in one patient, as well as the frequent combination with other functional diseases (for example, irritable bowel syndrome (IBS)) and gastroesophageal reflux disease (GERD). For the symptomatic treatment of functional dyspepsia, drugs of various groups are prescribed: gastric acid supressants, prokinetics, selective serotonin reuptake inhibitors, tricyclic antidepressants, as well as new drugs for this indication (H1 blockers, budesonide). The effectiveness of proton pump inhibitors, including in combination with prokinetics, has a high level of scientific evidence.